ANALISA UNSUR VISUAL KHAS INDONESIA DALAM ANIMASI ATLAS BOY ADVENTURES SERIAL HANTU ABU-ABU - Ni Made Sri Wahyuni Trisna; Hikma Novita Rahma (Jurnal Nawala Visual, 2021)
The rise of intellectual property, which is the right to own work in the creative industry, which has played an important role in efforts to increase the country's foreign exchange income, is now being pursued in the form of animated works which now function not only as entertainment but also as learning and commercial media. To increase the number of audiences, innovation needs to be done, selected Indonesian local wisdom to be implemented in the visual so that it makes it more attractive. This has succeeded in triggering the audience's curiosity which resulted in the audience being educated about the various Indonesian local wisdom that are adapted to it. Keywords: Intelectual Property, Animation, Visual, Local Wisdom, Innovation